2020
DOI: 10.1016/j.jdsr.2019.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Review of systematic reviews on mandibular advancement oral appliance for obstructive sleep apnea: The importance of long-term follow-up

Abstract: SummaryThe purpose of this review was to present the currently available information on oral appliance (OA) therapy for dentists, especially clinic-based dentists, to aid them in performing this treatment for the management of symptoms of obstructive sleep apnea (OSA). The clinical research evidence comprised of systematic reviews concerned with the mandibular advancement oral appliance (OAm). Continuous positive airway pressure (CPAP) is superior to OA therapy in improving OSA symptoms. It is necessary to sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 41 publications
0
5
0
1
Order By: Relevance
“…No obstante lo anterior, muchos profesionales desconocen los efectos adversos que éstos pueden tener en la oclusión. Los efectos son progresivos y significativos, observándose una mayor proinclinación de incisivos inferiores, reducción del overjet y overbite, mordida abierta posterior, y posible desarrollo de mordida invertida (41,42) . Estos efectos justifican una supervisión ortodóncica con controles al menos cada 6 meses, siendo el ortodoncista el profesional idóneo para ello (15) .…”
Section: Discussionunclassified
“…No obstante lo anterior, muchos profesionales desconocen los efectos adversos que éstos pueden tener en la oclusión. Los efectos son progresivos y significativos, observándose una mayor proinclinación de incisivos inferiores, reducción del overjet y overbite, mordida abierta posterior, y posible desarrollo de mordida invertida (41,42) . Estos efectos justifican una supervisión ortodóncica con controles al menos cada 6 meses, siendo el ortodoncista el profesional idóneo para ello (15) .…”
Section: Discussionunclassified
“…Possible reasons for these inconsistent results might include open labelling, lack of randomization, selection of the appliance being determined by resource availability (in the retrospective study by Lettieri et al [5]), and variations in the duration of follow-up. In a review of systematic reviews of bibloc versus monobloc appliances, Sato and Nakajima [12] reported a high degree of heterogeneity between study results, which precluded a valid meta-analysis. When the results of our 1-year study are compared with those of the preceding 8-week follow-up of the same sample of patients [8], one must also include time factors when interpreting outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…39 There is a significant positive correlation between oropharyngeal airway volume and mandibular length. 23,40 Increase in mandibular length by functional appliances has been demonstrated by Baccetti et al 41 and Marsico et al 42 A study evaluating the effects of skeletally anchored Forsus fatigue-resistant device (FFRD) and Herbst appliance reported a significant increase in the lower pharyngeal dimension with the former. 43 Celikoglu reported significantly increased oropharyngeal area measurements with both Herbst appliance and skeletally anchored Forsus FRD.…”
Section: Role Of Functional Appliances In Sdbmentioning
confidence: 92%
“…Oral appliance therapy during adulthood has clear dental and skeletal side effects with long-term use. 23 Therefore, if the identification of high-risk individuals is made early, it will serve a dual purpose i.e. enlargement of upper airway space along with addressing the malocclusion, facial dysmorphism, trauma to protruding incisors, and so on.…”
mentioning
confidence: 99%